Periostin promotes malignant potential by induction of epithelial‐mesenchymal transition in intrahepatic cholangiocarcinoma. Issue 10 (25th October 2017) - Mino, Masaaki; Kanno, Keishi; Okimoto, Kousuke; Sugiyama, Akiko; Kishikawa, Nobusuke; Kobayashi, Tomoki; Ono, Junya; Izuhara, Kenji; Kobayashi, Tsuyoshi; Ohigashi, Toshikazu; Ohdan, Hideki; Tazuma, Susumu
Abstract : Periostin, a secreted matricellular protein, has been reported to induce epithelial‐mesenchymal transition (EMT), which increases motility and invasiveness in various epithelial cancer cells. Periostin is also overexpressed in intrahepatic cholangiocarcinoma (ICC) and suggested to be a biomarker for tumor progression and poor prognosis; however, its functional role in ICC is not fully understood. Here, we investigated whether periostin influences malignant potential through the induction of EMT in ICC. Analyses of surgical resected ICC specimens revealed that the gene expression of periostin was significantly higher in ICC tumors than in adjacent nontumor liver tissues and was closely correlated with the expression of mesenchymal markers, including N‐cadherin, vimentin, and fibronectin. However, the expression level of periostin varied in each case. Consistently, the expression of periostin in HuH28 (an undifferentiated ICC cell) was markedly higher than in HuCCT‐1 (a moderately differentiated ICC cell). In addition, high‐level secretion of periostin into culture media was observed in HuH28 but not in HuCCT‐1. To identify the biological significance of periostin in EMT, gene silencing of periostin by small interfering RNA was performed in HuH28 cells. Periostin knockdown in HuH28 cells significantly down‐regulated mesenchymal markers and up‐regulated epithelial markers, suggesting the reversal of EMT, namely mesenchymal‐epithelial transition. Along with these changes, cell proliferation was significantly suppressed by 52%. In addition, cell migration and invasion were significantly suppressed by 62% and 61%, respectively, with reduced gene expression of matrix metalloproteinase 2. Interestingly, chemosensitivity to gemcitabine was also significantly improved by periostin depletion. Conclusion: Periostin plays an important role in the regulation of malignant potential through EMT and is suggested to be a novel target for the treatment of ICC. ( Hepatology Communications 2017;1:1099–1109)